PENEGAKAN HAK ASASI MANUSIA OLEH APARAT PENEGAK HUKUM: TANTANGAN NORMATIF DAN IMPLEMENTATIF DALAM SISTEM PERADILAN INDONESIA - Geofani Milthree Saragih; Mohd. Yusuf DM; Windy Widya; Jeki Rahmat Mustika; Gede Adi; Ahmad Angga (Universitas Labuhanbatu, 2025)
This study analyzes the enforcement of Human Rights (HR) by law enforcement authorities within the Indonesian judicial system, focusing on both normative and implementation-based challenges. The research employs a normative legal method with a descriptive-analytical approach. The legal materials examined include statutory regulations, court decisions, and legal doctrines and literature relevant to human rights protection and enforcement. The study applies a statutory approach and a conceptual approach to examine the legal framework governing human rights enforcement, the rule of law, and the accountability of law enforcement institutions. The findings indicate that, normatively, Indonesia possesses a relatively comprehensive legal framework for the protection of human rights. However, in practice, law enforcement continues to face significant obstacles, including inconsistencies in the application of law, weak accountability mechanisms, low levels of public trust, and the influence of structural and cultural factors within the judicial system. This gap between legal norms and their implementation has the potential to undermine substantive justice and effective human rights protection. Therefore, this study emphasizes the necessity of strengthening the integrity and capacity of law enforcement officials, ensuring consistency in law enforcement, and optimizing the role of human rights oversight institutions in order to realize a justice system that is fair, accountable, and oriented toward the protection of human rights.Keywords: Human Rights; Law Enforcement Authorities; Law Enforcement; Judicial System.